TYPE 1 KOUNIS SYNDROME: ALLERGIC VASOSPASTIC CARDIAC EVENT TRIGGERED BY CIPROFLOXACIN - Saher Shiza, MD (Elsevier, 2024)
Therapeutic Area: Preventive Cardiology Best Practices - clinic operations, team approaches, outcomes research Case Presentation: A 30-year-old male was brought to ED with sudden onset chest pain, diaphoresis, and lightheadedness, accompanied by itching, confusion, and collapse. Symptoms developed shortly after he took oral ciprofloxacin, which was prescribed by his physician because of a two-day history of flu-like symptoms. He denied any significant medical or family history of heart disease. He denied smoking, alcohol, or substance abuse.On evaluation, he was diaphoretic and tachypneic with blood pressure of 90/60 mmHg, heart rate of 58/minute, and oxygen saturation of 85%. The cardiovascular examination was unremarkable.Initial EKG showed ST-segment elevation in leads II, III, and aVF, suggestive of inferior wall myocardial infarction (1a). Urgent coronary angiography revealed normal coronary arteries with no significant thrombosis or stenosis (1b). Laboratory evaluations revealed elevated levels of troponin I (4.9 ng/ml) and creatine kinase MB (47 IU/L). He was managed with sublingual nitroglycerine, methylprednisolone, and intramuscular injection of epinephrine. Allergic work-up revealed elevated serum tryptase level (17/ng/ml). Over the subsequent hours, his condition improved. Repeat EKG showed sinus rhythm and resolution of ST-segment elevation (1c). Bedside echocardiography revealed no obvious segmental wall motion abnormalities. He remained hemodynamically stable throughout his admission, and he was advised to avoid fluoroquinolone antibiotics in future. Background: Kounis syndrome (KS), also known as allergic myocardial infarction, is a rare but potentially life-threatening condition characterized by acute coronary syndrome secondary to allergic reactions. Patients may present with normal coronary arteries (type I), established coronary artery disease (type II), or in-stent thrombosis or restenosis (type III). KS is most frequently triggered by medication and ciprofloxacin-induced KS-1 is rarely reported. We report a case of KS-1 triggered by ciprofloxacin. Conclusions: Ciprofloxacin is generally a well-tolerated drug and life-threatening hypersensitivity reactions are rare. To our knowledge, only four cases of ciprofloxacin-induced KS have been reported. Recognition of drug-induced allergic reactions as a potential trigger of acute coronary events is crucial for timely diagnosis and management. KS-1 should be included in the differential diagnosis of the acute coronary event with no coronary artery lesion, especially in patients with no previous cardiac history and recent ingestion of fluoroquinolones.